2016
DOI: 10.1038/ncomms13561
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RNAi screening identifies TMIGD3 isoform1 as a suppressor of NF-κB and osteosarcoma progression

Abstract: The ability of cancer cells to survive and grow in anchorage- and serum-independent conditions is well correlated with their aggressiveness. Here, using a human whole-genome shRNA library, we identify TMIGD3 isoform1 (i1) as a factor that suppresses this ability in osteosarcoma (OS) cells, mainly by inhibiting NF-κB activity. Knockdown of TMIGD3 increases proliferation, tumour formation and metastasis of OS cells. Overexpression of TMIGD3 isoform1 (i1), but not isoform3 (i3) which shares a common C-terminal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Consistently, high metastatic OS cell lines (KHOS/NP and MG63) tend to express lower levels of A3AR and TMIGD3 with lower IkB levels (indicating higher NF-kB activity), as compared with those in lowmetastatic cell lines (U2OS and Saos-2). 4 It should be noted that shRNAs for TMIGD3 and an antibody for TMIGD3 used in our study could not discriminate between the 2 isoforms of i1 and i3. Hence, it would be crucial for identifying and using specific shRNAs and antibodies that can distinguish these isoforms in the future.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Consistently, high metastatic OS cell lines (KHOS/NP and MG63) tend to express lower levels of A3AR and TMIGD3 with lower IkB levels (indicating higher NF-kB activity), as compared with those in lowmetastatic cell lines (U2OS and Saos-2). 4 It should be noted that shRNAs for TMIGD3 and an antibody for TMIGD3 used in our study could not discriminate between the 2 isoforms of i1 and i3. Hence, it would be crucial for identifying and using specific shRNAs and antibodies that can distinguish these isoforms in the future.…”
mentioning
confidence: 63%
“…Downregulation of TMIGD3 or A3AR by multiple shRNAs significantly increases malignant properties of different OS cell lines, including proliferation, migration, and sphere formation, as well as tumor progression and metastasis in nude mice. 4 Overexpression of A3AR and TMIGD3 i1, but not TMIGD3 i3, inhibits these malignant properties. Interestingly, similar to A3AR, TMIGD3 i1 suppresses activities of protein kinase A (PKA), PKB (also known as Akt), and NF-kB with minimal impacts on b-catenin and Erk1/2 activities, indicating that TMIGD3 i1 regulates overlapping signaling pathways with A3AR ( Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This alternative TSS results in a fusion product that includes the 116 Nterminal amino acids of A 3 R. Data on TMIGD3 are scarce, although one study revealed a role for TMIGD3 isoform 1 as a suppressor of NF-κB and osteosarcoma progression. 125 The ADORA3 gene's promoter region has not been extensively studied but reportedly does not contain a TATA box; however, the existence of a CCAT box is subject to debate. 126,127 Our analysis of the ADORA3 promoter region evidenced a CAAT box located 98 bp upstream of the TSS.…”
Section: Adora3mentioning
confidence: 99%